1992
DOI: 10.1016/0266-7681(92)90200-l
|View full text |Cite
|
Sign up to set email alerts
|

The Gymnast’s Wrist: Acquired Positive Ulnar Variance Following Chronic Epiphyseal Injury

Abstract: Five cases of symptomatic acquired positive ulnar variance are described. All cases occurred due to premature physeal closure of the growth plate in teenage girl gymnasts. All cases demonstrated ulnocarpal impingement, for which we describe a clinical test. Arthroscopic assessment of the wrist allowed us to assess the integrity of the TFCC (triangular fibrocartilaginous complex) and decide on the most appropriate surgery. Two patients needed distal ulna recession and one needed shaving for a TFCC perforation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
2
8

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(65 citation statements)
references
References 7 publications
4
51
2
8
Order By: Relevance
“…Deshmukh et al 12 reported that in ulnar shortening, the depth and the inclination of the sigmoid notch of the DRUJ caused changes in DRUJ congruity, joint contact area, and radioulnar separation. Tolat et al 18 suggested that ulnar shortening in patients with a reverse orientation of the DRUJ (negative sigmoid notch and ulnar seat inclination angles) is difficult without disturbing the configuration of the joint. Sagerman et al 14 agreed with this concept and added that similar problems may develop in patients with large differences in the inclination of their joint surfaces.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deshmukh et al 12 reported that in ulnar shortening, the depth and the inclination of the sigmoid notch of the DRUJ caused changes in DRUJ congruity, joint contact area, and radioulnar separation. Tolat et al 18 suggested that ulnar shortening in patients with a reverse orientation of the DRUJ (negative sigmoid notch and ulnar seat inclination angles) is difficult without disturbing the configuration of the joint. Sagerman et al 14 agreed with this concept and added that similar problems may develop in patients with large differences in the inclination of their joint surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…The ulnar-shortening procedure, however, is usually indicated for patients with an ulnar plus variance. [1][2][3][4][5][6][7]18 The distribution of ulnar variance and sigmoid notch inclination in this study may not be representative of normal subjects but of the patients who have had this procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Pain was scored with a visual analogue score (VAS), 0 meaning minimal pain, 10 meaning maximal pain. Tolat's test (test of ulnocarpal impingement) 18 was performed and furthermore the DRUJ was tested for instability and pain by manual translation in radio-ulnar and palmar-volar direction, the DRUJ-translationtest. 8 Range of motion of both wrists was measured with a goniometer.…”
Section: Clinical Evaluationmentioning
confidence: 99%
“…Ocasionalmente, estas superficies articulares pueden ser paralelas al eje longitudinal del antebrazo (ARCD neutra), o pueden estar anguladas en sentido contrario (ARCD invertida). La configuración articular es especialmente importante en casos que requieren acortamiento cubital, puesto que el acortamiento cubital en el caso de ARCD invertida puede causar mayor choque entre la escotadura sigmoidea y la superficie articular del cúbito 14 . Signos radiológicos de artritis de la ARCD deberían ser específicamente investigados al realizar radiografías de rutina.…”
Section: Radiografías Estándarunclassified
“…El mecanismo involucra la impactación de la estiloides cubital contra el polo proximal del piramidal. La longitud relativa de la estiloides cubital se calcula usando el índice de la apófisis estiloides cubital 14 . Una estiloides excesivamente larga tiene una longitud total mayor a 6 mm 31 .…”
Section: A Choqueunclassified